HUBUNGAN ALOKASI WAKTU PERJALANAN DENGAN WAKTU AKTIVITAS PENGGUNA SEPEDA MOTOR BERDASAR DATA CATATAN HARIAN - Kharisma, Alan Hardi; Joewono, Tri Basuki (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Activity-based travel shows detail on each trip and activity performed by an individual during a given period of time. The purpose of this study is to describe the travel time and activity time workers of motorcycle users and to analyze the relation between activity time and travel time. The results of the analysis show that the highest average of activity time budget occurs at the activity of sleeping and working, namely 431.33 minutes and 356.10 minutes. Analysis of the relation between duration of activity time and travel time indicates that there is a relation, either weekdays, and the male and female gender. The analysis found that at the weekend found that the timing of activities and travel time does not have a significant relation.